Influência do fornecimento de suplemento energético em ovinos sobre pastagem de azevém em sistema de integração lavoura-pecuária - Pivatto, Daniela Rita Deparis (2016)
The term integration lavoura- livestock is an ancient practice performed since the domestication of animals and plants of the time by man. The aim of this study was to evaluate the effect of supplementation in the field cutting sheep and sheep pen through the average daily gain, animal gain, productivity and stocking, and finally assessment of housing in integrated crop-livestock system. The experiment was conducted at the State University of Central West of Paraná, campus CEDETEG, in the South Central region of the state of Paraná, in Guarapuava. For implementation of grazing ryegrass (Lolium multiflorum Lam.), Used the basic fertilization for the ryegrass seeding using 250 kg ha-1 formulated 0-20-20 (N, P2O5, K2O) . 36 animals were used, from the crossing of breeds Texel x Ile de France, age 45 days of life. power systems consisted of unsupplemented systems, supplementation at night, when they were gathered into the fold and supplementation in the morning, the field. Supplementation provided was derived from the process of grinding the whole corn cob (CEC), being provided 1% of live animal weight. Protein metabolic profile and energy were used to obtain information on the nutritional status of animals, conducted through blood tests. It was observed that there was significant difference between food systems, animals supplemented the night, had better gain per area, average daily gain and average gain per period. The values of the analysis of forages was for the NDF and ADF different values at the beginning of the evaluations, but with the passage of time the pasture presented senescence having no more changes. Already in biochemical profiles were more significant changes in the analysis of urea, which can be explained by nutrient cycling. Once animals ingest the pasture rich in nutrients, eliminating it ends up via the feces and urine excess thus returning nutrients to the soil. Integrated systems associated with supplementation lead to producing an improvement in their alternative income, and benefits to animals and soil. Thus opening a new chance to produce in a ustainable way, maximizing natural resources.